2019
DOI: 10.1002/cncr.32552
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐phenotype acute leukemia: A cohort and consensus research strategy from the Children’s Oncology Group Acute Leukemia of Ambiguous Lineage Task Force

Abstract: BACKGROUND:Optimal chemotherapy for treating mixed-phenotype acute leukemia (MPAL) and the role of hematopoietic stem cell transplantation (HSCT) remain uncertain. Major limitations in interpreting available data are MPAL's rarity and the use of definitions other than the currently widely accepted criteria: the World Health Organization 2016 (WHO2016) classification. METHODS: To assess the relative efficacy of chemotherapy types for treating pediatric MPAL, the Children's Oncology Group (COG) Acute Leukemia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…However, all known MPAL treatment data that supports upfront ALL-based therapy is retrospective, and can be challenging to interpret given the changing definitions of this disease. 5,18,19 The current Children's Oncology Group (COG) study AALL1732 After relapse, tacrolimus was switched to sirolimus, in an attempt to target NRAS downstream by inhibiting mTOR. 17 mTOR inhibitors in combination with additional agents have been studied in AML and other advanced cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all known MPAL treatment data that supports upfront ALL-based therapy is retrospective, and can be challenging to interpret given the changing definitions of this disease. 5,18,19 The current Children's Oncology Group (COG) study AALL1732 After relapse, tacrolimus was switched to sirolimus, in an attempt to target NRAS downstream by inhibiting mTOR. 17 mTOR inhibitors in combination with additional agents have been studied in AML and other advanced cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, all known MPAL treatment data that supports upfront ALL‐based therapy is retrospective, and can be challenging to interpret given the changing definitions of this disease. 5 , 18 , 19 The current Children's Oncology Group (COG) study AALL1732 (NCT03959085), is the very first clinical trial to enroll MPAL patients prospectively. This study is designed to treat all de novo MPAL patients with ALL‐directed therapy, but allows for patients with a poor treatment response to switch to AML chemotherapy followed by allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MPAL are classified based on lineage-specific immunophenotypic markers determined by flow cytometry, immunohistochemistry, or cytochemistry and primary molecular alteration, and are considered by most co-operative groups to be high-risk leukemias [ 5 ]. The majority of MPAL present as B-lymphoid/myeloid (in about 2/3 cases), with a T-lymphoid/myeloid immunophenotype being the second most common presentation.…”
Section: Classification Of Mpalmentioning
confidence: 99%
“…However, the true prevalence and survival can be difficult to determine given the various diagnostic criteria utilized, lack of a centralized review of cases, and treatment protocols that are based on results from retrospective studies. The Children’s Oncology Group Acute Leukemia of Ambiguous Lineage Task Force reported that routine institutional flow cytometry was insufficient for the diagnosis of MPAL in about 15% of children, which further highlights the diagnostic challenge faced by oncologists [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal therapy for this subtype of leukemia has not been established, especially in pediatric patients and the role of hematopoietic stem cell transplantation (HSCT) in first remission remains contentious 6 . Even though HSCT in first complete remission (CR‐1) for adult patients with MPAL is recommended, recent pediatric report by Orgel et al suggests no benefit for HSCT in CR1, particularly for those with favorable features 9 . Thus, the aim of this retrospective, population‐based study was to analyze biological and clinical features and treatment results in children diagnosed with MPAL in centers of Polish Pediatric Leukemia/Lymphoma Study Group between 2007 and 2018.…”
Section: Introductionmentioning
confidence: 99%